Formation of hydrogen with phototrophic green microalgae alons Chlamydomonas reinhardtii Dang., 119 in the conditions of deficiency of elements of sulfur and magnes - Труш, К. Б. (Problems of Environmental Biotechnology, 2019)
The formation of hydrogen by green microalgae Chlamydomonas reinhardtii Dang., 119 was studied under conditions of magnesium and sulfur deficiency on a tris-acetate-phosphate medium. It is established that hydrogen is synthesized more with a lack of magnesium, slightly less in the absence of sulfur and a simultaneous deficiency of magnesium and sulfur. It was revealed that the deficiency of magnesium and sulfur significantly worsens the state of the photosystem and reduces the level of hydrogen synthesis Chlamydomonas reinhardtii Dang., 119.